Butyltin(IV) Benzoates: Inhibition of Thioredoxin Reductase, Tumor Cell Growth Inhibition, and Interactions with Proteins. Issue 2 (23rd December 2012) - Navakoski de Oliveira, Kely; Andermark, Vincent; von Grafenstein, Susanne; Onambele, Liliane A.; Dahl, Gregor; Rubbiani, Riccardo; Wolber, Gerhard; Gabbiani, Chiara; Messori, Luigi; Prokop, Aram; Ott, Ingo
Abstract Thioredoxin reductase (TrxR) is overexpressed in cancer cells and is therefore a putative cancer target. Inhibition of this enzyme is considered an important strategy for the development of new chemotherapeutic agents with a specific mechanism of action. Organotin compounds have been described as experimental antitumor agents, yet their mechanism of action remains largely unknown. Based on the outcome of a virtual screening study, various di‐ and tri‐n‐butyltin(IV) carboxylates were synthesized, and their biological properties were evaluated. All synthesized compounds were able to inhibit TrxR selectively within the micromolar range and showed potent antitumor activity against HT‐29 and MCF‐7 cancer cell lines. Moreover, tin(IV) organometallics were found to strongly induce apoptosis in the BJAB lymphoma cell line. Mass spectrometry and atomic absorption spectroscopy experiments revealed metal binding to proteins, and efficient cellular uptake was observed using a di‐n‐butyltin(IV) complex as an example.